Optical-Electrical Characteristics and Carrier Dynamics of Semi-Insulation GaAs by Terahertz Spectroscopic Technique - 韩小卫 侯磊 杨磊 王志全 赵萌萌 施卫 (Chinese physics letters, 2016)
OaAs has been widely used to fabricate a variety of optoelectronic devices by virtue of its superior performance, and it is very important to accurately measure its electrical and optical properties. In this study, a semi- insulation （SI） GaAs wafer is investigated by the terahertz （THz） non-destructive testing technology. Using an air biased coherent generation and detection THz time domain spectroscopy system, the THz time domain waveform and spectrum of SI-GaAs are obtained by the time domain spectroscopy module, and its optical- electrical characteristics including complex refractive index, permittivity and dielectric loss angle are calculated. Its carrier lifetime is measured by the optical-pump THz-probe module, and the THz pulse induced intervalley scattering in photo-excited SI-GaAs is discussed.